Mirroring Duterte - Ilagan, Karol; Fabricante, Agatha; Fabro, Christine (Kasarinlan: Philippine Journal of Third World Studies, 2020)
This case study focuses on the role of the local media in creating an environment favorable for forwarding the political propaganda against illegal drugs in Davao City. The local newspaper of Davao, the Mindanao Daily Mirror appeared to serve as a mouthpiece of those in power in Davao City rather than as an inquirer, watchdog, or representative of the Davaoeños. Through reviewing 256 news reports and interviewing journalists, this research casts light on how the media was used in antidrug campaigns and how it framed the narratives behind the operations in relation to the drug war in Davao City.
Keywords: Mindanao Daily Mirror; Rodrigo Duterte; Davao City; local media; antidrug campaigns; political propaganda